Penerapan Prinsip Keadilan Sosial dalam Pengelolaan Zakat, Infak, dan Sedekah: Perspektif Ekonomi Islam Kontemporer - Mahera, Rofiqo Meili; Jamal, Khairunnas (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
The purpose of this study is to analyze the problem of zakat, infaq and sedekah, the social values of zakat, infaq and sedekah, the relationship between zakat, infaq and sedekah with the social values of society. The method used in this study is library research to investigate and review literature related to the concept of zakat, infaq, and sedekah and its relationship with the social values of society. Data were collected from various sources of information such as literature, scientific articles, manuscripts, and written works that are in accordance with the topic being studied. The results of this study include; (1) Zakat is an obligation in Islam that requires Muslims to give part of their wealth to those who are entitled (mustahik zakat). Infaq is a voluntary contribution for goodness or humanity, while sedekah is an act of giving without considering the status of the recipient, (2) The Social Values of Zakat, Infaq, and Sedekah include; justice values, solidarity values, empathy values and social welfare values, (3) The relationship between zakat, infak, and alms with social values of society includes: (a) redistribution of wealth and social justice, (b) building solidarity and social concern, (c) helping to eradicate poverty and increase welfare, (d) economic empowerment and independence, (e) strengthening religious and moral values.